Characterisation and modelling of gallium nitride power semiconductor devices dynamic on-state resistance - Li, Ke; Evans, Paul; Johnson, Mark (IEEE, 2017)
GaN-HEMTs suffer from trapping effects which increases device ON-state resistance (RDS(on)) above its theoretical value. This increase is a function of the applied DC bias when the device is in its OFF state, and the time which the device is biased for. Thus, dynamic RDS(on) of different commercial GaN-HEMTs are characterised at different bias voltages in the paper by a proposed new measurement circuit. The time-constants associated with trapping and detrapping effects in the device are extracted using the proposed circuit and it is shown that variations in RDS(on) can be predicted using a series of RC circuit networks. A new methodology for integrating these RDS(on) predictions into existing GaN-HEMT models in standard SPICE simulators to improve model accuracy is then presented. Finally, device dynamic RDS(on) values of the model is compared and validated with the measurement when it switches in a power converter with different duty cycles and switching voltages.